Preclinical Development of CAR T Cells with Antigen-Inducible IL18 Enforcement to Treat GD2-Positive Solid Cancers. - Fischer-Riepe, Lena; Kailayangiri, Sareetha; Zimmermann, Katharina; Pfeifer, Rita; Aigner, Michael; Altvater, Bianca; Kretschmann, Sascha; Völkl, Simon; Hartley, Jordan; Dreger, Celine; Petry, Katja; Bosio, Andreas; et al. (Clinical Cancer Research, 2024)
PURPOSE: Cytokine-engineering of chimeric antigen receptor-redirected T cells (CAR T cells) is a promising principle to overcome the limited activity of canonical CAR T cells against solid cancers. EXPERIMENTAL DESIGN: We developed an investigational medicinal product, GD2IL18CART, consisting of CAR T cells directed against ganglioside GD2 with CAR-inducible IL18 to enhance their activation response and cytolytic effector functions in the tumor microenvironment. To allow stratification of patients according to tumor GD2 expression, we established and validated immunofluorescence detection of GD2 on paraffin-embedded tumor tissues. RESULTS: Lentiviral all-in-one vector engineering of human T cells with the GD2-specific CAR with and without inducible IL18 resulted in cell products with comparable proportions of CAR-expressing central memory T cells. Production of IL18 strictly depends on GD2 antigen engagement. GD2IL18CART respond to interaction with GD2-positive tumor cells with higher IFNγ and TNFα cytokine release and more effective target cytolysis compared with CAR T cells without inducible IL18. GD2IL18CART further have superior in vivo antitumor activity, with eradication of GD2-positive tumor xenografts. Finally, we established GMP-compliant manufacturing of GD2IL18CART and found it to be feasible and efficient at clinical scale. CONCLUSIONS: These results pave the way for clinical investigation of GD2IL18CART in pediatric and adult patients with neuroblastoma and other GD2-positive cancers (EU CT 2022- 501725-21-00). See related commentary by Locatelli and Quintarelli, p. 3361.
EVALuna2:565266